ANALISIS KUALITAS AIR DI PERAIRAN DANAU TOBA KECAMATAN PANGURURAN, KABUPATEN SAMOSIR - Silaban, Winarto; Silalahi, Mastiur Verawaty (Universitas Pendidikan Ganesha, 2021)
Lake Toba is a lake located in Samosir Regency, North Sumatra Province with a surface area of 1,124 km2 (112,400 ha). Lake Toba is located at a geographical position 2°41′N 98°53′E / 2.68°N 98.88°E with an altitude of 995 above sea level. The purpose of this study was to determine water quality in terms of chemical, physical, and biological parameters, as well as the status of water quality in Lake Toba. Determination of the sample point using the